2016
DOI: 10.1371/journal.pone.0150645
|View full text |Cite
|
Sign up to set email alerts
|

How Different Medical School Selection Processes Call upon Different Personality Characteristics

Abstract: BackgroundResearch indicates that certain personality traits relate to performance in the medical profession. Yet, personality testing during selection seems ineffective. In this study, we examine the extent to which different medical school selection processes call upon desirable personality characteristics in applicants.Methods1019 of all 1055 students who entered the Dutch Bachelor of Medicine at University of Groningen, the Netherlands in 2009, 2010 and 2011 were included in this study. Students were admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
22
0
2
Order By: Relevance
“…Students who previously chose to participate in a selection procedure, for which coping with stress and being able to combine studies with other activities are important, may become energized by and be able to cope better with the pressure of clerkships. Students who had participated in selection have been found to be more emotionally stable and conscientious than students who did not (Schripsema et al 2016). The group of Year-1 students that had not participated in selection was rather small; this might explain why these differences did not reach significance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Students who previously chose to participate in a selection procedure, for which coping with stress and being able to combine studies with other activities are important, may become energized by and be able to cope better with the pressure of clerkships. Students who had participated in selection have been found to be more emotionally stable and conscientious than students who did not (Schripsema et al 2016). The group of Year-1 students that had not participated in selection was rather small; this might explain why these differences did not reach significance.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, limited evidence supports the hypothesis that students who have participated in selection outperform those who have not. Motivation, as reflected in the preparation for selection, has been suggested as one reason why students who have participated might perform better (Schripsema et al 2014(Schripsema et al , 2016Wouters et al 2016), but this assumption has not yet been investigated. The second research question addressed in this study is: Is participation in selection associated with differences in motivation, engagement and preclinical and clinical performance?…”
Section: Introductionmentioning
confidence: 99%
“…For example, personality might play a role. A recent study at this university indicated that selection-accepted students scored high on conscientiousness and extraversion, and low on neuroticism, characteristics that were shown to predict success in medical school (Schripsema et al 2016). Additionally, efficient study strategies and time management skills might play a role (Schripsema et al 2015;West and Sadoski 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Few studies that relate personality traits with the existent medical selection tools show that different selection processes call upon different personality traits (Azman et al 2014;Griffin and Wilson 2012;Jerant et al 2012;Schripsema et al 2014;Schripsema et al 2016). For instance, if MMI performance is associated with extraversion (Griffin and Wilson 2012;Jerant et al 2012), it has been shown that the admitted medical students with higher top pre-university grades have higher conscientiousness scores when compared to the lottery-admitted group (Schripsema et al 2014;Schripsema et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if MMI performance is associated with extraversion (Griffin and Wilson 2012;Jerant et al 2012), it has been shown that the admitted medical students with higher top pre-university grades have higher conscientiousness scores when compared to the lottery-admitted group (Schripsema et al 2014;Schripsema et al 2016). Nevertheless, the research on the selected personality traits with regard to the application of direct personality assessment by self-report personality tests is practically non-existent.…”
Section: Introductionmentioning
confidence: 99%